2020
DOI: 10.1186/s12903-020-01160-0
|View full text |Cite
|
Sign up to set email alerts
|

Association between adverse childhood experiences, bullying, self-esteem, resilience, social support, caries and oral hygiene in children and adolescents in sub-urban Nigeria

Abstract: Background: Adverse childhood experiences (ACE) and bullying have negative effects on oral health. Promotive assets (resilience, self-esteem) and resources (perceived social support) can ameliorate their negative impact. The aim of this study was to determine the association between oral diseases (caries, caries complications and poor oral hygiene), ACE and bully victimization and the effect of access to promotive assets and resources on oral diseases. Methods: This was a secondary analysis of data collected t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 88 publications
(92 reference statements)
2
11
0
5
Order By: Relevance
“…It also showed no signi cant association with DMFT score and gingival score. These ndings are consistent with Folayan et al (11) who clinically examined Nigerian children, in schools, from ages 6-16, and revealed that less than 4% of the sample developed caries and had dental complications. Furthermore, this was the only study with similar sample selection and examination methodology that showed no association between tooth decay and ACE which; supports the current ndings.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…It also showed no signi cant association with DMFT score and gingival score. These ndings are consistent with Folayan et al (11) who clinically examined Nigerian children, in schools, from ages 6-16, and revealed that less than 4% of the sample developed caries and had dental complications. Furthermore, this was the only study with similar sample selection and examination methodology that showed no association between tooth decay and ACE which; supports the current ndings.…”
Section: Discussionsupporting
confidence: 90%
“…These ndings suggest that ACEs may act as a risk indicator for dental caries and periodontal disease (9,10). However, among 6 to 16 years old Nigerian pupils, there was no association between dental caries, poor oral hygiene, oral disease complications and ACE (11). Nevertheless, little to scarce research assessed the link between ACE and oral health status of Egyptian children whose level of oral diseases and ACE may be different from western countries and who have high level of caries.…”
Section: Introductionmentioning
confidence: 98%
“…The available evidence on caries in Nigeria indicates that the prevalence in adolescents 10–16 years old varies by settlement type. Caries prevalence ranges from 5.9% in sub-urban Nigeria [ 20 ], to 12.2% in a rural population [ 21 ] and from 11.2% to 15.5% in urban populations [ 21 23 ]. Gingivitis however appears far more prevalent, with 95% of 11–16-year-old students in an urban secondary school showing evidence of periodontitis [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although there is some oral health data in Nigeria that may include the 10–19-year adolescent demographic, these data are often generated to reflect children under 10 or under 15 years of age. Some data are available on the epidemiology of caries in the 10–16-year age group [ 20 23 , 41 – 43 ]; however, there is no data on caries and periodontal diseases in older adolescents 17–19-year-old, and limited data on periodontal diseases among 10–16-year-olds [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the consequences of bullying can range from physiological to psychological, and victims are considered anxious, insecure, sensitive, withdrawn, and with low self-esteem as adolescents [Barasuol et al, 2017]. Conversely, good oral health can facilitate healthy smiles and less bully victimization [Folayan et al, 2020]. Although this statement sounds logical, there is no scientific evidence to support this notion.…”
Section: Introductionmentioning
confidence: 99%